Resource conflict, collective action, and resilience: An analytical framework - Ratner, Blake D.; Meinzen-Dick, Ruth S.; May, Candace; Haglund, Eric (International Food Policy Research Institute, 2010)
In developing countries where access to and use of renewable natural resources essential to rural livelihoods are highly contested, improving cooperation in their management is increasingly seen as an important element in strategies for peacebuilding, conflict prevention, and longer-term social-ecological resilience. While researchers have made important advances in recent years in assessing the role of environmental resources as a causal factor in civil conflict, analysis of the positive potential of collective natural resource management efforts to reduce broader conflict is less developed. In particular, there is a need for analytical tools that not only describe stakeholder interactions and outcomes but also yield practical guidance on what development practitioners and policy makers can do to promote such goals. Addressing this need, we present a framework focused on the links between collective action, conflict prevention, and social-ecological resilience. Building on the institutional analysis and development (IAD) model, and incorporating principles from the sustainable livelihoods approach and resilience theory, the framework is applicable across multiple scales of analysis, linking local stakeholder dynamics to the broader institutional and governance context. Accounting for both formal and informal relationships of power and influence, as well as values and stakeholder perceptions alongside material interests, the framework aims to provide insight into the problem of (re)building legitimacy of resource management institutions in conflict-sensitive environments. We present the elements of the framework and outline its application in stakeholder-based problem assessment and planning, participatory monitoring and evaluation, and multi-case comparative analysis.